2015
DOI: 10.1155/2015/171356
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Aqueous Extract Induces Hepatocellular Carcinoma Cells Arrest in S Phase via JNK Signaling Pathway

Abstract: Huaier aqueous extract, the main active constituent of Huaier proteoglycan, has antihepatocarcinoma activity in experimental and clinical settings. However, the potential and associated antihepatoma mechanisms of Huaier extract are not yet fully understood. Therefore, in this study, we aimed to elucidate the inhibitory proliferation effect of Huaier extract on apoptosis and cycle of HepG2 and Bel-7402 cells. Our data demonstrated that incubation with Huaier extract resulted in a marked decrease in cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…We think the roles of the ERK and p38 are partly associated with cell type. On the contrary, JNK signaling pathway was considered to induce HCC cell cycle arrest and induced HCC apoptosis (27). In the present study we also found that emodin may suppress the activation of JNK mildly, this indicates the JNK pathway may not play a major role in emodin's effect.…”
Section: Discussionsupporting
confidence: 38%
“…We think the roles of the ERK and p38 are partly associated with cell type. On the contrary, JNK signaling pathway was considered to induce HCC cell cycle arrest and induced HCC apoptosis (27). In the present study we also found that emodin may suppress the activation of JNK mildly, this indicates the JNK pathway may not play a major role in emodin's effect.…”
Section: Discussionsupporting
confidence: 38%
“…Recently, increasing attentions have been paid to anti-tumor drugs originating from TCM 7 . A lot of clinical applications have revealed that Huaier has a good anti-tumor activity, especially in HCC 27 28 29 . Nevertheless, the underlying mechanisms of anti-HCC effect of Huaier remain ill defined.…”
Section: Discussionmentioning
confidence: 99%
“…Our result was consistent with a previous finding that Huaier suppressed cell viability and induced G0/G1 cell-cycle arrest in breast cancer cell lines 12 . However, there are several studies reporting that Huaier induced cell-cycle arrest in G2/M phase in human cervical cancer cells 30 and human melanoma cells 31 , and caused S phase arrest in human hepatocellular carcinoma cell lines HepG2 and Bel-7402 28 . This phenomenon may be interpreted by the complicated effects of Huaier on different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Wang X et al and Zhang N et al reported that cellcycle arrest occurs in breast cancer MCF-7 and MDA-MB-231 cells and human umbilical vein endothelial cells in the G0/G1 phase [16,31]. Zhang C found that Huaier extract induces hepatocellular carcinoma cell HepG2 and Bel-7402 arrest in S phase [32]. In conclusion, Huaier extract causes cell apoptosis and induces cancer cell arrest in different phases.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 91%